Fluids along the North Anatolian Fault, Niksar basin, north central Turkey: Insight from stable isotopic and geochemical analysis of calcite veins. (August 2017) - Sturrock, Colin P.; Catlos, Elizabeth J.; Miller, Nathan R.; Akgun, Aykut; Fall, András; Gabitov, Rinat I.; Yilmaz, Ismail Omer; Larson, Toti; Black, Karen N.
Abstract: Six limestone assemblages along the North Anatolian Fault (NAF) Niksar pull-apart basin in northern Turkey were analyzed for δ 18 OPDB and δ 13 CPDB using bulk isotope ratio mass spectrometry (IRMS). Matrix-vein differences in δ 18 OPDB (−2.1 to 6.3‰) and δ 13 CPDB (−0.9 to 4.6‰) suggest a closed fluid system and rock buffering. Veins in one travertine and two limestone assemblages were further subjected to cathodoluminescence, trace element (Laser Ablation Inductively Coupled Plasma Mass Spectrometry) and δ 18 OPDB (Secondary Ion Mass Spectrometry, SIMS) analyses. Fluid inclusions in one limestone sample yield Th of 83.8 ± 7.3 °C (±1σ, mean average). SIMS δ 18 OPDB values across veins show fine-scale variations interpreted as evolving thermal conditions during growth and limited rock buffering seen at a higher-resolution than IRMS. Rare earth element data suggest calcite veins precipitated from seawater, whereas the travertine has a hydrothermal source. The δ 18 OSMOW-fluid for the mineralizing fluid that reproduces Th is +2‰, in range of Cretaceous brines, as opposed to negative δ 18 OSMOW-fluid from meteoric, groundwater, and geothermal sites in the region and highly positive δ 18 OSMOW-fluid expected for mantle-derived fluids. Calcite veins at this location do not record evidence for deeply-sourced metamorphic and magmatic fluids, an observation that differs from what is reported for the NAF elsewhere along strike. Graphical abstract: Highlights: Geochemical signals of fluid flow through fractured carbonate rocks are reported. The Turkish North Anatolian Fault (Niksar portion) does not record deep fluids. Calcite veins record events unrelated to their active plate boundary position. Ion microprobe δ 18 OPDB transects across calcite veins show fine-scale variations. Mineralizing fluid that reproduces fluid inclusion T has Cretaceous brine δ 18 OSMOW .